SINTESIS ETIL ASETAT DARI HASIL FERMENTASI KULIT SINGKONG (Manihot Esculenta L) DENGAN ASAM ASETAT MENGGUNAKAN KATALIS ASAM - Tri Eva Lidiawati; Chairul Saleh; Alimuddin Alimuddin (PROSIDING SEMINAR KIMIA, 2018)
A study on the synthesis of ethyl acetate from fermented cassava peel (Manihot esculenta L) with acetic acid using acid catalyst has been done. Determination of the ratio of ethanol content with the addition of yeast bread and yeast tape, also to know the rendement of ethanol and ethyl acetate contained in cassava skin. Cassava leaf flour is hydrolyzed by using concentrated hydrochloric acid (HCl) then tested by reducing sugar content by nelson somogyi method and analyzed by using UV-Vis spectrophotometry. The hydrolysis result is divided into two parts and added yeast tape and bread yeast is also added nutrient NPK each and fermented for 5 days. The fermentation results were distilled off and analyzed using Chromatography Gas (GC). The obtained ethanol is reacted with acetic acid and sulfuric acid catalyst in the esterification reaction to obtain ethyl acetate. The esterification results were analyzed by IR spectroscopy. Ethanol obtained from Chromatography Gas (GC) analysis of 13% and esterification results from IR spectroscopic analysis showed the presence of ester (ethyl acetate) formed. Keywords: Cassava Leather, Fermentation, Esterification, Ethyl Acetate.